DEVELOPING A CONSTRUCTIVISM APPROACH IN MATHEMATICS LEARNING - Nursupiamin; Lilies N.Tangge, Afadil (Adisam Publisher, 2024)
Mathematics learning characterized by constructivism emphasizes building one's own understanding actively, creatively and productively based on previous knowledge and experience. The teacher's task in applying constructivism to mathematics learning is not only to transmit ideas to students, but also to change the conceptions they have to develop them, therefore teachers need to pay attention to students' initial conceptions before learning begins, this aims to make it easier for students in the process. processing new knowledge that will be received. In the implementation stage of constructivist mathematics learning, teachers must understand aspects of mathematics learning that are based on constructivist theory. In this regard, a number of aspects related to mathematics learning, namely (1) students construct mathematical knowledge by integrating the ideas they have, (2) mathematics becomes more meaningful because students understand it, (3) students' strategies are better assessed, and ( 4) students have the opportunity to discuss and exchange experiences and knowledge with their friends. Based on these aspects, as much as possible, the implementation of constructivism in mathematics learning must start from basic education for children.